Benzo[a]phenoxazinium chlorides possessing chlorinated terminals: synthesis, photophysics and photostability studies - Carvalho, Marcello M. T. (2013)
Fluorescent probes are essential in fluorescence based bioanalytical techniques that have been widely used in a diversity of scientific areas, including environment, biology, pharmacy and medicine. They are involved in studies with cells, proteins, enzyme activity, DNA and RNA, among others. The interaction of fluorophores with targets can be accomplished by covalent or non-covalent linkages, carried out through reactive groups suitable for chemical binding to biomolecules or by a variety of mechanisms, such as electrostatics, hydrophobics and hydrogen-bonding, respectively.1 As a continuation of our research in the synthesis and characterisation of fluorescence probes,2 the present work aims to describe the preparation of a new set of benzo[a]phenoxazinium chlorides possessing isopentylamino, (2-cyclohexylethyl)amino and phenethylamino substituents at 5-position and 3-chloropropyl groups at the amine in 9-position of the polycyclic system (Figure 1). The later terminals allow covalent labelling of targets by nucleophilic substitution, besides the intrinsic non-covalent ability of benzo[a]phenoxazinium chlorides synthesized. Fundamental photophysics as well as photochemical stability studies were carried out and will be discussed.